2022
DOI: 10.1097/dss.0000000000003442
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pain After Mohs Micrographic Surgery: A Prospective Study

Abstract: BACKGROUND Mohs micrographic surgery (MMS) is a widely used technique for removal of cutaneous tumors. The procedure is well-tolerated with little surgical or postoperative pain. OBJECTIVE This study examined pain levels after Mohs surgery throughout the first week of recovery and the relation to patient demographics, lesion characteristics, surgery details, and postoperative analgesia. METHODS A 2-year prospective observational study included patients who underwent MMS. Patients rated the severity of postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In our study, 4 patients out of 695 (0.575%), reported chronic pain at the biopsy site 3 months after the procedure (see Table 2 for pain and patient characteristics). All four were women, which is congruent with most other publications that describe a higher rate of post-operative pain in women, e.g., female gender was associated with more severe postoperative pain after root-canal treatment in a cohort of 270 patients [21], and after Mohs Micrographic Surgery [19].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, 4 patients out of 695 (0.575%), reported chronic pain at the biopsy site 3 months after the procedure (see Table 2 for pain and patient characteristics). All four were women, which is congruent with most other publications that describe a higher rate of post-operative pain in women, e.g., female gender was associated with more severe postoperative pain after root-canal treatment in a cohort of 270 patients [21], and after Mohs Micrographic Surgery [19].…”
Section: Discussionsupporting
confidence: 88%
“…However, various studies indicate that the Mohs procedure (for treating skin cancer, where individual layers of skin are removed and examined to determine if they are cancerfree) is comparable to oral soft tissue biopsy, because it is generally non-painful and well-tolerated by all genders across all ages [19,20]. In our study, 4 patients out of 695 (0.575%), reported chronic pain at the biopsy site 3 months after the procedure (see Table 2 for pain and patient characteristics).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in a study by Shir-az et al, 16 pain levels following MMS are strongest in the first postoperative day, but in general MMS is considered nonpainful and well-tolerated. It is common practice in our clinics to educate patients regarding the expected pain levels and to recommend the use of nonopioid based oral analgesics in the days following surgery.…”
Section: Discussionmentioning
confidence: 94%
“…However, previous studies have demonstrated increased postoperative pain levels in certain anatomical locations, such as the scalp, forehead, nose, and ear, particularly for the first 3 postoperative days. 8,9 Additionally, the type of reconstruction is known to influence postoperative pain levels, with flaps and grafts, including STSG, resulting in more postoperative pain compared with primary closure. 8,9 In line with these reports, this study found that patients in the STSG group experienced significantly more pain than those in the SIH group during the first 3 days after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Additionally, the type of reconstruction is known to influence postoperative pain levels, with flaps and grafts, including STSG, resulting in more postoperative pain compared with primary closure. 8,9 In line with these reports, this study found that patients in the STSG group experienced significantly more pain than those in the SIH group during the first 3 days after surgery. Nonetheless, the daily mean reflected pain was overall mild to moderate, and well tolerable with over-the-counter analgesics such as acetaminophen.…”
Section: Discussionmentioning
confidence: 99%